Assessment of morning sleep propensity with lemborexant in adults with insomnia disorder in a randomized, placebo-controlled crossover study. Issue 1 (2nd July 2021) - Mayleben, David; Rosenberg, Russell; Pinner, Kate; Hussein, Ziad; Moline, Margaret
Abstract: Objective: To evaluate effects of lemborexant (LEM), a dual orexin receptor antagonist, on next-morning sleep propensity assessed by a modified Multiple Sleep Latency Test (M-MSLT) in adults with insomnia disorder. Methods: Study 107 (E2006-A001-107) was a phase 1, randomized, double-blind, four-period crossover study. Subjects ( n = 69) received oral single-dose placebo, LEM 5 mg (LEM5), and LEM 10 mg (LEM10) at bedtime in periods 1–3 in a randomized crossover and open-label flurazepam 30 mg in period 4. After an 8-hour overnight sleep opportunity, the M-MSLT measured average sleep onset latency (SOL). Mean change from baseline in average SOL versus placebo of −6.0 min or more was considered clinically meaningful. Other sleep propensity assessments included the proportion of subjects with average SOL >6 min shorter than placebo. LEM plasma concentrations, safety, and tolerability were also assessed. Results: M-MSLT assay sensitivity was confirmed by a clinically meaningful decrease in average SOL with flurazepam versus placebo (least squares mean [LSM] difference –6.06 min; 1-sided p < 0.0001). In contrast, decreases in average SOL with LEM5 (LSM difference vs. placebo –1.15 min; 1-sided p = 0.0262) and LEM10 (–3.48 min; p < 0.0001) did not meet the predefined threshold for a clinically meaningful effect (LEM5, –2.12; LEM10, –4.46). Some individuals did experience higher sleep propensity (average SOL >6.0 min shorter than placebo), particularly with LEM10 (LEM10, 29.4%; LEM5, 13.2%). Conclusions: In contrast to flurazepam, LEM5 and LEM10 did not show clinically meaningful mean increases in next-morning sleep propensity versus placebo. The possibility that some subjects may experience residual morning effects cannot be excluded. Clinical trial registration: ClinicalTrials.gov, NCT02350309